Omo Biosphere Reserve, Current Status, Utilization of Biological Resources and Sustainable Management (Nigeria) - Isichei, Augustine O. (UNESCO, 2014)
Omo Biosphere Reserve, which derives its name from River Omo that traverses it, is located between latitudes 6o35' to 7 o 05' N and 4o 19' to 4o 40' E in the Ijebu area of Ogun State southwestern Nigeria. The Reserve was constituted in 1925 and covers about 130 500 hectares, about 20 km from the Atlantic coast in its southern most parts. Geologically the Reserve lies on crystalline rocks of the undifferentiated basement complex which in the southern parts is overlain by Eocene deposits of sand, clay and gravel. The terrain is undulating and the maximum elevation of 150m above sea level is towards the west which the lowest parts of the Reserve are in the south where the River Omo joins River Oni, the Reserve's eastern boundary, before flowing into the Lekki Peninsular on the Atlantic coast. There are swamps in the south especially near the junction of the two rivers. The soil is tropical ferruginous (Ferric luvisol, according to FAO nomenclature). The mean annual rainfall ranges from about 1600 to 2000 mm with two annual peaks in June and September, with November and February being the driest months. The Reserve is in the mixed moist semi-evergreen rainforest zone. The northern parts of the Reserve is relatively dry forest with typical species such as Sterculia rhinopetala while Nauclea diderrichii and Terminalia superba are common in the wetter central parts. In the wet forests on sandy swampy soils in the south Lophira and trees in the Meliaceae family are common.